Attitudes towards Electronic Voting and Commenting in Business, Private and Public Meetings - Rafajac, Ozren; Kaluža, Marin; Ogrizović, Dario (Journal of Ecohumanism, 2024)
This paper analyses attitudes toward meeting app features that support collaboration in business, private, and public affairs and offers an entity relationship diagram of an electronic meeting system (EMS) that can be successfully applied in those three spheres. An empirical research was conducted on a sample of 120 (N) respondents from the Republic of Croatia, while the research instrument was an online questionnaire containing 15 mandatory and 2 open-ended questions. The analysis revealed a statistically significant positive and strong relationship between organisations that should use an EMS but do not use it and organisations that spend too much time and resources on managing official meetings (τb = .576, p < .01). 48.3% of respondents claim that their organisations should use an EMS in business operations, while 57.5% of respondents believe that the EMS improves productivity. 65% of respondents agree and strongly agree that it is desirable to use authorised electronic voting in public affairs, while 33.4% of respondents agree and strongly agree that they would like to use the electronic voting system in private affairs. The conducted research shows that followers are more inclined to vote anonymously (U = 1109, z = -2.947, p = .003, r = .07) and comment anonymously (U = 1178, z = -2.580, p = .010). , r = .06) from their leaders. For this reason, authors have designed an entity relationship diagram of an EMS that supports both anonymous and transparent interaction.